Pengembangan Sistem Rencana Anggaran Biaya Pada CV. Widjaya Sido Dadi - Eka Paksi; Hikmatulloh Hikmatulloh (Masoem University, 2025)
The Bill of Quantity (RAB) is an essential document in the execution of construction projects, functioning to detail all cost requirements. This study aims to design and implement a web-based RAB information system at CV. Widjaya Sido Dadi. The main issue faced by the company is that the RAB preparation process is still carried out manually, making it prone to calculation errors and time-consuming. The development method used is Agile with an iterative approach, which allows the system to be developed gradually according to user needs. The system is built using PHP as the programming language and MySQL as the database, and it is designed using the Unified Modeling Language (UML) approach. The test results show that the system improves operational efficiency, speeds up the budgeting process, and minimizes errors in project cost calculations. With the implementation of this system, the company is expected to find it easier to prepare the RAB.